Transporte térmico em nanofitas de grafeno dopadas com N, B e SI - Kipper, Ana Claudia (2017)
The recent progress of the research on carbon nanostructures and the issue of thermal management have established a great demand in relation to the scientific understanding of thermal transport in these nanomaterials. In addition, these materials serve as fundamental blocks for the creation of new nanostructures with different physical properties that can be modified and controlled for specific applications. Experimental studies in this area are promising, but a greater understanding of these new structures and their properties is deficient. In this context, molecular dynamics simulation is a powerful tool for calculations of thermal conductivity and vibrational spectrum of the phonons. The objective of this work is to propose new nanostructures based on carbon, to obtain a better understanding of its thermal properties, in order to verify the applicability in nanodevices. In the first part of this thesis, we present the results of the thermal conductivity and the vibrational spectrum of the phonons in graphene sheets and graphene nanoribbons pristine, where we observe that the thermal conductivity in nanoribbons presents a reduction in relation to graphene sheets and that this behavior is due to the effect of edges. We also analyzed the behavior of thermal conductivity as a function of the graphene nanoribbons length and width, where we observed an increase in thermal conductivity as the sample size increased. In addition, we observed that the thermal conductivity presents a behavior of dependence with the temperature of the system. After characterizing the thermal properties of pristine graphene nanoribbons, we focused on possible strategies to control the heat transfer in these materials.One possibility is to explore the edge saturation and the doping of the graphene nanorinnons. Thus, we investigate the thermal conductivity in nanoribbons with saturated edges with hydrogen atoms and nanoribbons doped with nitrogen, boron and silicon atoms. The estimated thermal conductivity in saturated/doped nanoribbons is drastically reduced. A vibrational density analysis of the phonons is performed to explain this difference, showing that the density of the vibrational modes of the phonons are different when compared to pristine type nanoribbons.